SPOT on life skills: a model life skills curriculum for middle school students with disabilities - Curtin, Christine (2019)
School-based occupational therapy practitioners (OTPs) have distinct expertise in providing occupation-based interventions. OTPs are called to employ these skills to improve postsecondary outcomes (employment, independent living, postsecondary education) of students with disabilities, as a result of the rising rate of students with disabilities served under the Individuals with Disabilities Education Act (IDEA 2004) surmounting 14% of all public school students in the United States in 2017-2018, and only marginal increases in otherwise poor postschool outcomes of students with disabilities, (U.S. Department of Education, 2019; Test, et al., 2009). The domains of practice in which OTs support clients include activities of daily living, instrumental activities of daily living, rest/sleep, education, work, play, leisure, and social participation (American Occupational Therapy Association, 2014). These are all domains that are relevant to transition planning for adolescents with disabilities, however, current evidence suggests that OTs do not play a significant role in providing transition-based services to school aged youth across the United States (Mankey, 2011). Utilizing Kolb’s experiential learning theory and current research evidence, it is evident that the lack of a widely recognized life skills curriculum, lack of training on the use of occupation-based interventions, and limited use of occupation-based interventions by OTs in middle schools, are negatively impacting the life skills development of students with disabilities. In response, the author created SPOT on Life Skills, an evidence-based theory-driven model for a middle school life skills curriculum. The curriculum will be delivered by an interdisciplinary team including an occupational therapist, a special education teacher, and a speech and language pathologist, who will collaborate together and with the students and their families. The curriculum model will consist of a multifaceted intervention approach including self-care and independent living skills training, social skills training, work readiness, and a work-based experience to increase student independence and improve long-term transition outcomes (Test et al., 2009). The intention of the program, beyond exposing students to a variety of life skills, is to increase OT’s involvement in transition planning and use of occupation-based interventions in the middle school setting. It is anticipated that SPOT on Life Skills, will influence stakeholders to advocate for life skills/transition programming utilizing collaborative occupation-based practices.